أنشطة التعليم العالي في المواقع الالكترونية الرسمية خلال جائحة كورونا(جامعة جامعة أم البواقي نموذجا) - قالي, جنات; عزوز, شافية (جامعة الوادي - University of Eloued, 2022)
نظرا لانتشار جائحة كوفيد19، تم استئناف الأنشطة البيداغوجية حصريا بنمط التعليم عن بعد ابتداء من 23 أوت 2020. ولهذا أصبحت المواقع الإلكترونية الرسمية للجامعات كنوع من أنواع المواقع التي تنشئها الجامعات لتقديم خدمة متنوعة وتحقيق أهداف محددة؛ والتي من شأنها توفير المعلومات والأخبار والإنتاج العلمي وكل ماهو مستجد في الجامعة نظرا لطبيعة نشاطها الذي يهم المستخدمون خصوصا جمهور الجامعة منهم وعلى رأسهم فئتي الأساتذة والطلبة، لأجل ذلك ركزنا اهتمامنا على دراسة حالة للموقع الرسمي لجامعة أم البواقي خلال الجائحة من حيث طريقة نشرهما وعرض مضامين لأنشطة التعليم العالي التي تحدث على مستوى المؤسسة الجامعية، باستخدام الملاحظة والمقابلة لجمع البيانات حول الموقع وخلصت الدراسة إلى توفر الموقع الالكتروني على اللغتین الفرنسیة والانجليزية والعربیة، والاعتماد في عرضها على وسائط محددة لنقل المعلومات، ویعرض النصوص التي تقدم تفاصیل الموضوع وحیثیاته، والصور الثابتة على شكل ملفات قابلة للتحمیل (docx, pdf ,doc)، أما أبرز مواضیعه هي عروض المنح، لملتقیات، المسابقات المهنیة والعلمیة،...، وبهذا فهي تستهدف الطلبة، الأساتذة، الإداریون و الجمهور الخارجي للمؤسسة الجامعية. الكلمات المفتاح : أنشطة التعليم العالي؛ موقع الكتروني؛ الجامعة؛ جائحةكورونا. Abstract: Due to the spread of the Covid 19 pandemic, pedagogical activities have been resumed exclusively in the style of distance education from August 23, 2020. That's why the official websites of universities have become a kind of site created by universities to provide a diverse service and achieve specific objectives, which will provide information, news, scientific production and everything new at the university due to the nature of their activity, which is of interest to users, especially the university audience, including the professors and students, so we focused our attention on a case study of the official website of oum el bouaghi University during the pandemic in terms of the way they are published and present contents of higher education activities that occur at the university level, using observation and interview to collect Data about the site and the study concluded the availability of the website on french, English and Arabic languages, relying on its presentation on specific media for the transmission of information, and presents texts that provide the details of the topic and its activities, and fixed images in the form of files downloadable docx, pdf ,doc), while the most prominent topics are grant offers, for selections, professional and scientific competitions, ... And so it targets students,the university institution.Using the note and the interview to collect data about the official website.
Higher education activities on official websites during the Corona pandemic )University oum el bouaghi model)
مقال
Keywords: أنشطة التعليم العالي، موقع الكتروني، الجامعة، جائحة كورونا; higher education activities, website, university, pandemic.